Optimization of Protoplast Preparation Conditions in Lyophyllum decastes and Transcriptomic Analysis Throughout the Process - Xiaobin Li; Ying Qin; Yufei Kong; Samantha Chandranath Karunarathna; Yunjiang Liang; Jize Xu (Journal of Fungi)
Protoplasts are essential tools for genetic manipulation and functional genomics research in fungi. This study systematically optimized protoplast preparation conditions and examined transcriptional changes throughout the preparation and regeneration processes to elucidate the molecular mechanisms underlying the formation and regeneration of protoplasts in Lyophyllum decastes. The results indicated an optimal protoplast yield of 5.475 × 106 cells/mL under conditions of fungal age at 10 days, digestion time of 2.25 h, enzyme concentration of 2%, and digestion temperature of 28 °C. The Z5 medium supplemented with L. decastes mycelial extract achieved a high regeneration rate of 2.86. RNA-seq analysis revealed 2432 differentially expressed genes (DEGs) during protoplast formation and 5825 DEGs during regeneration. Casein kinase I, cytochrome P450 (CYP52), and redox-regulated input receptor (PEX5) were significantly upregulated during the protoplast stage, while β-1,3-glucan synthase (SKN1), chitin synthase (CHS2), hydrophobin-1, and hydrophobin-2 showed significant upregulation during the protoplast regeneration phase. These findings provide a reference for the efficient preparation and regeneration of protoplasts and offer new insights into the molecular mechanisms of protoplast formation and cell wall regeneration in fungi.